2005
DOI: 10.1159/000089445
|View full text |Cite
|
Sign up to set email alerts
|

Proven Strategies to Reduce Cardiovascular Mortality in Hemodialysis Patients

Abstract: Background: In hemodialysis patients, left ventricular hypertrophy (LVH) correlates with mortality. The reason for LVH in uremics is multifactorial. The primary objective of our study was to investigate the effects of a multi-interventional treatment strategy on LVH. Methods: In 230 ambulatory patients, including patients with coronary artery disease, diabetes, diastolic and systolic dysfunction, we continued optimized cardiac therapy (β-blockers, angiotensin-converting enzyme inhibitors and angiotensin recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…Hampl et al (14) confi rmed signifi cant reduction of LVMI, LVEDD and ejection fraction increase, but no left atrial size decrease in a group of 230 patients due to intensifi cated antihypertensive treatment (beta blockers, inhibitors of angiotensin-converting enzyme and AT1 receptors) and correction of anaemia. They suppose that many patients do not get complete antihypertensive treatment to decrease cardiovascular risk.…”
Section: Discussionmentioning
confidence: 97%
“…Hampl et al (14) confi rmed signifi cant reduction of LVMI, LVEDD and ejection fraction increase, but no left atrial size decrease in a group of 230 patients due to intensifi cated antihypertensive treatment (beta blockers, inhibitors of angiotensin-converting enzyme and AT1 receptors) and correction of anaemia. They suppose that many patients do not get complete antihypertensive treatment to decrease cardiovascular risk.…”
Section: Discussionmentioning
confidence: 97%
“…The main finding of the mentioned studies [32][33][34] is that a multi-interventional approach, which combines optimized cardiac/antihypertensive therapy with ␤ -blockers, ACE inhibitors/ARBs with complete correction of renal anemia by erythropoietin and intravenous iron, resulted in a significant reduction of the LVMI. The metabolic acidosis was optimally corrected, therefore, no potassium problems could be observed with our cardiac/ antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since the presence and/or progression of LVH have emerged as an independent prognostic factor, LVH has become accepted as a surrogate parameter for morbidity/mortality outcomes in uremic patients. Hampl et al [32][33][34] found by multivariate analysis that the presence of LVH at baseline, full correction of renal anemia and cardiac/antihypertensive therapy were significant and independent predictors of significant LVH regression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations